PENGARUH PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2017 - Esih Jayanti; Rafiq Ahady; Sudiyono (JURNAL EKONOMI, 2019)
This study aims to determine effect Profitability, Liquidity and Firm Size of Capital Structure of the Manufacturing companies listed on Indonesia Stock Exchange for 4 years from 2014-2017. The population of this research is manufacturing companies which are still listed in Indonesia Stock Exchange period 2014-2017. Sampling technique using purpose sampling, and obtained by 45 Manufacturing Company. The results of this study show that: Profitability significant effect on Capital Strructure, Liquidity significant effect on Capital Strructure, Firm Size significant effect on Capital Strructure. Simultaneously Profitability, Liquidity and Firm Size of Capital Structure of the Manufacturing Companies significant effect to Capital Strructure. Keywords : Profitability, Liquidity, Firm Size and Capital Strructure